Magnetic coupling in ferromagnetic semiconductor (Ga,Mn)As/(Al,Ga,Mn)As bilayers - Wang, M.; Wadley, P.; Campion, R.P.; Rushforth, A.W.; Edmonds, K.W.; Gallagher, B.L.; Charlton, T.R.; Kinane, C.J.; Langridge, S. (American Institute of Physics, 2015)
We report on a study of ferromagnetic semiconductor (Ga,Mn)As/(Al,Ga,Mn)As bilayers using magnetometry and polarized neutron reflectivity (PNR). From depth-resolved characterization of the magnetic structure obtained by PNR, we concluded that the (Ga,Mn)As and (Al,Ga,Mn)As layers have in-plane and perpendicular-to-plane magnetic easy axes, respectively, with weak interlayer coupling. Therefore, the layer magnetizations align perpendicular to each other under low magnetic fields and parallel at high fields.